Serotonin-Exacerbated DSS-Induced Colitis Is Associated with Increase in MMP-3 and MMP-9 Expression in the Mouse Colon - Menglu Chen; Lei Gao; Pan Chen; Dandan Feng; Yalin Jiang; Yongchao Chang; Jianjun Jin; Fong-Fong Chu; Qiang Gao (Mediators of Inflammation)
Background. 5-HT enhances dextran sulfate sodium- (DSS-) induced colitis and is involved in inflammatory bowel disease (IBD). Matrix metalloproteinases (MMPs) play roles in the process of intestinal inflammation. Aims. To examine whether 5-HT induces MMPs expression in mouse colon to enhance DSS-induced colitis. Materials and Methods. C57BL/6J (B6) mice were treated with either low-dose (1.0 mg/kg) or high-dose (2.0 mg/kg) 5-HT by enema, low-dose (1.0%) or high-dose (2.5%) DSS, or combined low-dose (1.0%) DSS and (1.0 mg/kg) 5-HT. Mouse colitis was analyzed. MMPs and tissue inhibitors of MMPs (TIMPs) mRNA were measured by real-time quantitative RT-PCR in mouse colon and in human Caco-2 cells and neutrophils. MMP-3 and MMP-9 protein levels were quantified from immunohistochemistry (IHC) images of mouse colons. Results. 5-HT exacerbated DSS-induced colitis, low-dose 5-HT induces both MMP-3 and MMP-9, and high-dose 5-HT only increased MMP-3 mRNA expression in mouse colon. Mouse colon MMP-3 and MMP-9 protein levels were also elevated by 5-HT treatment. The MMP-2, TIMP-1, and TIMP-2 mRNA levels were increased in the inflamed colon. 5-HT induced MMP-3 and MMP-9 mRNA expression in Caco-2 and human neutrophils, respectively, in vitro. Conclusion. 5-HT induced MMP-3 and MMP-9 expression in mouse colon; these elevated MMPs may contribute to DSS-induced colitis.